2006
DOI: 10.1093/humrep/del149
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized study to assess the benefit of partial zona pellucida digestion before frozen-thawed embryo transfers

Abstract: Within the constraints of our protocol, partial enzymatic digestion of zona pellucida by pronase was not related with any benefit of the FET outcome especially concerning the implantation ability of frozen-thawed embryos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 41 publications
1
33
0
6
Order By: Relevance
“…However, to the best of our knowledge, no single study has been able to demonstrate sufficient evidence favourable to AH, and the current research conclusions are not unanimous (6)(7)(8)(9)(10)(11)(12)(13). In a large meta-analysis, Martins et al showed that laser-AH (LAH) is currently one of the best, safest and most effective AH methods (14).…”
Section: Introductionmentioning
confidence: 83%
“…However, to the best of our knowledge, no single study has been able to demonstrate sufficient evidence favourable to AH, and the current research conclusions are not unanimous (6)(7)(8)(9)(10)(11)(12)(13). In a large meta-analysis, Martins et al showed that laser-AH (LAH) is currently one of the best, safest and most effective AH methods (14).…”
Section: Introductionmentioning
confidence: 83%
“…assisted hatching, may be useful for frozen-thawed embryo transfer. However, there are only a few randomized studies focused on the benefit of assisted hatching following frozen-thawed embryo transfer that have reported controversial results with decreased [2], similar [3][4][5] or increased [6][7][8][9] implantation rates in the assisted hatching group compared with the control group. This is likely related to different assisted hatching techniques (chemical, enzyme or laser) and different methods of zona pellucida manipulation (thinning or opening), in addition to differences in the study design, patient characteristics, and selection criteria.…”
Section: Introductionmentioning
confidence: 99%
“…assisted hatching (AH), may be useful for frozen thawed embryo transfer. However, very recent studies focused on the benefit of AH following frozen thawed embryo transfer reported controversial results with decreased [2], similar [3,4] or increased [5,6] implantation rates in the AH group compared to the control group. Different types of AH have been developed.…”
Section: Introductionmentioning
confidence: 99%